2022
DOI: 10.1002/eji.202149656
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection activates dendritic cells via cytosolic receptors rather than extracellular TLRs

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19), an infectious disease characterized by strong induction of inflammatory cytokines, progressive lung inflammation, and potentially multiorgan dysfunction. It remains unclear how SARS-CoV-2 infection leads to immune activation. The Spike (S) protein of SARS-CoV-2 has been suggested to trigger TLR4 and thereby activate immunity. Here, we have investigated the role of TLR4 in SARS-CoV-2 infection and immunity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Intracellular viral sensors play master roles in identifying SARS-CoV-2, leading to effective type I IFNs and cytokine responses. Moreover, it is possible for SARS-CoV-2 to escape TLR perception, which may account that, the body has not yet established effective immunity against the virus at the initial stage of SARS-CoV-2 invasion ( van der Donk et al, 2022 ). This leads to inefficient DCs activation and subsequent abnormal inflammatory responses.…”
Section: Tlrs Sensing Of Sars-cov-2mentioning
confidence: 99%
“…Intracellular viral sensors play master roles in identifying SARS-CoV-2, leading to effective type I IFNs and cytokine responses. Moreover, it is possible for SARS-CoV-2 to escape TLR perception, which may account that, the body has not yet established effective immunity against the virus at the initial stage of SARS-CoV-2 invasion ( van der Donk et al, 2022 ). This leads to inefficient DCs activation and subsequent abnormal inflammatory responses.…”
Section: Tlrs Sensing Of Sars-cov-2mentioning
confidence: 99%
“…It is also important to take into account that SARS-CoV-2 seems to escape direct recognition by TLR4, as shown by van der Donk et al [ 102 ], which could explain the inefficient immunity to SARS-CoV-2 during the early stages of infection. Indeed, plasmocytoid dendritic cells (pDCs) seem to sense SARS-CoV-2 via the following two distinct innate immune pathways: the endosomal TLR7 pathway activated through viral RNA, which leads to type I IFN production, and the TLR2 pathway triggered by the recognition of the viral envelope protein, inducing IL-6 production [ 103 ].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Still, others also report a lack of authentic activation in their model systems. For instance, monocyte-derived dendritic cells, which abundantly express TLR4 and other TLRs, were not activated by authentic SARS-CoV-2 particles, S pseudoparticles or recombinant S protein ( van der Donk et al, 2022 ). While the evidence points towards S1 or S2 as the trigger for a proinflammatory response, and TLR4 or TLR2 as the primary mediator of this response ( Khan et al, 2021 ; Shirato and Kizaki, 2021 ; Zhao et al, 2021 ; Frank et al, 2022 ), another study suggested a role for the SARS-CoV-2 E protein in the production of inflammatory cytokines ( Zheng et al, 2021 ).…”
Section: The Role Of Tlr4 and Spike In The Proinflammatory Response T...mentioning
confidence: 99%